Produtividade de grãos, forragem e composição bromatológica do trigo de duplo propósito cv. BRS Tarumã sob manejos de corte e adubação nitrogenada - Ramella, João Ricardo Pompermaier (2012)
In the constant quest for sustainability of agriculture production systems, many studies are conducted with the objective of seeking alternatives to the problems generated by the use indiscriminate production systems. To present work aimed to study the effect on grain yield and forage in dual-purpose wheat cv BRS Tarumã under different managements related to nitrogen and number of cuts. The experiment was conducted in two trials during the period March 2011 to January 2012 red Eutrophyc Latossol area located at the experimental farm of Prof Dr. Antônio Carlos dos Santos Pessoa, city of Marechal Cândido Rondon - PR. The trial was conducted in a randomized block design with 12 treatments obtained by combinations of the numbers of cuts and increasing doses of nitrogen in four replications. We studied the yield and yield components, as well as forage productivity and its chemical composition, noting that for all variables significant interaction of doses of nitrogen and the number of cuts. The grain yield and yield components were responsive to the levels of nitrogen topdressing, as well as forage production and quality